Pemberian Terapi Latihan, Ultrasound (US) Serta Transcutaneous Electrical Nerve Stimulation (TENS) Pada Pasien Osteoarthritis Knee Bilateral - Kunti Latifah (Syntax Corporation Indonesia, 2022)
Osteoarthritis (OA) is a degenerative disease that develops slowly and is widespread, its prevalence increases with age of the patient. The purpose of this study was to control the pain felt by the patient and improve the functional ability of the patient's daily activities. This research includes a case study conducted in one of the hospitals in the city of Surakarta on a patient Ny. S, 63 years old, works as a housewife. The patient complains of pain when moving from squatting to standing, especially during the prostration to standing movement during prayer, namely prayer. Pain is felt when it disappears when resting and not doing too much strenuous activity. Patients treated for 2 x / week in 3 weeks, one therapy followed for 30 minutes. Patients are given therapy in the form of exercise therapy, ultrasound and dozens. Pain was measured using the Visual Descriptive Scale (VDS), and the Western Ontario and McMaster Universities Arthritis Index (WOMAC) to measure the patient's functional activity. Physiotherapy modalities such as Quadriceps Setting Exercises, Passive Stretching, Ultrasound (US), and Transcutaneous Electrical Nerve Stimulation (TENS) given 4 times have not been able to improve daily functional activities and there is a slight reduction in pain.